The use of digital project management solutions by project businesses: a case study of a selected platinum mine in the Limpopo province - Mahlo, Kgothatso Erens; Spencer, John Peter (JOURNAL OF CONSTRUCTION PROJECT MANAGEMENT AND INNOVATION, 2022)
There have been specific technological shifts globally in the discipline of project management, which include the implementation of Project Management Software (PMS) packages. PMS is a pliant software solution that is used for managing projects: administrating, planning, organising, resources managing, document managing, costs, and time management. The awareness and adoption of PMS is unclear, especially in developing countries. This study has examined the awareness and adoption levels of digital project management solutions by project businesses at a selected opencast platinum mine in the Limpopo Province. The study also investigated project management challenges, and the impediments of adoption and the readiness of project businesses to adopt digital project management solutions. A quantitative research survey was distributed and emailed to project businesses at mine, where 110 project businesspersons participated in this study. SPSS v26.0 software was utilised to process data. The study publicised that the level of awareness of digital project management tools is higher than the level of adoption. Several barriers were identified as the impediments of adopting digital project management tools. It is recommended in the study that PMS developers should consider integrating with other systems that could enhance project management processes. It is also recommended that they should consider creating different packages for all business sizes and project magnitudes. Keywords: Digital project management tools, project business, Project Management Software (PMS), project management